Transformation of Creative Process Through Self-Translation: A Comparative Analysis of Abdullah Hussain’s Novels - Amin, Sadia; Farhat, Perveen Akhter; Maitlo, Sonal Khan; Soomro, Abdul Rehman (Pakistan Journal of Humanities and Social Sciences, 2023)
Self-translation mentions more precisely to the creativity of bilingual and multilingual authors who decided to translate the texts they have written or published in one of the languages they master, into other languages. Recent researches prove that self-translation has an extended convention, a prevalent sensation in numerous cultures and is strictly related to the illustration of self-identity. In this perspective, this study covers the relation between self-translation and transformation of creative process through relative study of Abdullah Hussain’s “Oddas Nasslian” and its self-translated portrayal “The weary Generation’’. The researchers observe the translation strategies implemented by Abdullah Hussain that directed to the deformation in the text and make prominent the transformation of author’s creativity as represented by his selection plans. The data analysis is based on macro-textual level. The study discloses that during translation, the text has been transformed and altered differently on both macro textual levels. With the help of in-depth written analysis of self-translated text, this research unveils transformation procedure of self by introducing the results into larger socio-cultural perspective. The study in hand also reveals that self- translation enjoys more liberty with the role of “creativity” being clearer than in cases of translation by others.